ANALISIS PENGARUH LITERASI USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP KEPUTUSAN UNTUK MELAKSANAKAN PRINSIP-PRINSIP EKONOMI DAN BISNIS ISLAM (STUDI DI KECAMATAN CIAMPEA, KABUPATEN BOGOR) - Sugiarto, Rendi; Thantawi, Tubagus Rifqy; Putra, Bayu Purnama (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Micro, Small and Medium Enterprises (MSMEs) are businesses that have wide employment opportunities, provide broad economic services, encourage economic growth, and play a role in realizing the nation. The purpose of this study was to determine the characteristics of sharia entrepreneurs in micro, small and medium enterprises (MSMEs) regarding MSME Literacy in carrying out their activities in accordance with Islamic economic and business principles. This type of research is quantitative with a sample of 75 respondents. The sampling technique used was the Random Sampling technique with the Tabachic & Fidell method. The analytical method used is multiple linear regression analysis using SPSS version 25 software. The results of this study indicate the effect of the independent variables consisting of reading literacy, understanding literacy, and practical literacy, which together have a real and positive effect. However, reading literacy is more dominant which has a real and positive effect on decisions in carrying out Islamic economics and business principles, with a regression coefficient value of 0.622 which means that if the practice literacy variable increases by one unit, then the value of the decision to implement Islamic economic and business principles will increased by 0.622. practicing literacy can encourage MSMEs in determining decisions to implement Islamic economic and business principles.